The remembered soldier - Daanje, Anjet, 1965- (New Vessel Press, 2025)
An extraordinary love story and a captivating novel about the power of memory and imagination: Flanders 1922. After serving as a soldier in the Great War, Noon Merckem has lost his memory and lives in a psychiatric asylum. Countless women, responding to a newspaper ad, visit him there in the hope of finding their spouse who vanished in battle. One day a woman, Julienne, appears and recognizes Noon as her husband, the photographer Amand Coppens, and takes him home against medical advice. But their miraculous reunion doesn't turn out the way that Julienne wants her envious friends to believe. Only gradually do the two grow close, and Amand's biography is pieced together on the basis of Julienne's stories about him. But how can he be certain that she's telling the truth? In The Remembered Soldier, Anjet Daanje immerses us in the psyche of a war-traumatized man who has lost his identity. When Amand comes to doubt Julienne's word, the reader is caught up in a riveting spiral of confusion that only the greatest of literature can achieve.